Caring for Mothers and their newborns- Midwives’ role - Bhakare, Samruddhi; Kadam, Manisha; Gopalkrishnan, Sripriya (Innovational: Journal of Nursing and Healthcare, 2024)
Proceedings of the Regional level CNE (Continuing Nursing Education), 29th June 2017, Sadhu Vaswani College of Nursing, Pune. Caring for Mothers and their newborns -Midwives' role", the Regional level was held on 29th June 2017 at Sadhu Vaswani College of Nursing, Pune. CNE was conducted with the intention to increase the nurses’ knowledge regarding Midwives roles, their independent practice issues and knowledge of Newborn Characteristics, Care and Resuscitation and most important to learn and gain from this CNE was Nurses Importance and role in Midwifery and Newborn Care. A total of 100 participants pre-registered from all over Maharashtra State. The participants included Chief guest, nursing faculty, clinical nurses specially Obstetrics, Gynecology and Neonatal department and students from various nursing colleges and hospitals. The conference programme was focused on - current trends in Midwifery, midwifery-led care, care pre, during and post delivery of mothers, their newborn care, and emergency care.